PENINGKATAN AKTIFITAS BELAJAR PEMROGRAMAN VISUAL BERBASIS DESKTOP MELALUI PEMANFAATAN ALAT PERAGA PROGAM APLIKASI INVENTARIS BAGI SISWA SMK NEGERI 5 SURAKARTA - Basori Basori; Dona Asm’ul Khusnawan (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2017)
The background of this study is the lack of students activity in the conventional learning on desktopbased visual programming subjects. As a result, many students do not understand the material provided by the teacher. The purpose of this study is to determine the enhancement in the learning activity of student by utilizing props inventory application program for students of SMK Negeri 5 Surakarta. The research was conducted by using class action research with 2 cycles. The subject of study taken is the class XI RPL A in SMK Negeri 5 Surakarta. The research object is the quality of the learning process, ie the activity of learning. The experiment was conducted on 2nd semester academic year 2013/2014. The data collection techniques used were observation and interviews. The Data analysis technique using the qualitative analysis refers to the analysis model Miles and Huberman. Based on the result of the research , we can conclude that an increase in the learning activity of precycle student learning is 34,43%, in cycle 1 is 71,65%, and increased to 77,04% in cycle 2. It is proved that the props inventory application program helps students to increase the learning activity on a desktop-based visual programming subject .